2009
DOI: 10.1007/bf03179214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of bile salt hydrolase inLactobacillus casei Zhang

Abstract: Bile salt hydrolase (BSH) is one of the genes relevant to bile tolerance. Biochemical assay showed that Lactobacillus casei Zhang was able to deconjugate sodium taurocholate during growth. To explore the possible relationship between BSH activity and bile tolerant ability, we cloned and determined full-length DNA sequence of the BSH gene in L. casei Zhang, and monitored its expression pattern under the stress of bile salts. The DNA sequence consists of 1181 nucleotides; the putative protein includes 338 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
7
2
Order By: Relevance
“…On the other hand, the results of the qRT-PCR experiments indicated that proteins involved in cell protection and modification of the cell membrane as well as key components of central metabolism may play an important role in bile salts resistance of L. casei Zhang. However, none of the putative bile salt hydrolase homologs in L. casei Zhang reported in previous studies (Zhang et al, 2009) showed differential expression during the bile treatments as revealed by 2-DE in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…On the other hand, the results of the qRT-PCR experiments indicated that proteins involved in cell protection and modification of the cell membrane as well as key components of central metabolism may play an important role in bile salts resistance of L. casei Zhang. However, none of the putative bile salt hydrolase homologs in L. casei Zhang reported in previous studies (Zhang et al, 2009) showed differential expression during the bile treatments as revealed by 2-DE in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…A concentration of 0.5% (w/v) bile salts resulted in up to a 4-fold down-regulation in the expression of bsh gene in all strains compared with its expression in the control (without bile salts). This result differs considerably from the finding of Zhang et al (2009) who reported that L. casei strain Zhang exhibited a more than one fold change in expression when grown with 0.5% (w/v) bile salts.…”
Section: Expression Of the Homologous Bsh Genescontrasting
confidence: 99%
“…Bile salt hydrolase (BSH) is a protein expressed by bacteria commonly found in the intestinal tract that can deconjugate bile salts and also have the added positive effect of lowering serum cholesterol levels and reducing the risk of obesity and arthrosclerosis in the host ( Wang et al, 2011 ). BSH activity has been found in L. casei but is not always present ( Gilliland and Speck, 1977 ; Zhang et al, 2009 ; Wang et al, 2011 ). There is conflicting evidence whether or not BSH increases tolerance to bile salts with many studies finding a correlation ( Moser and Savage, 2001 ; Wang et al, 2011 ) while many others have failed to find correlation between BSH activity and bile tolerance ( Begley et al, 2005 ; Bustos et al, 2012 ).…”
Section: Bile Stressmentioning
confidence: 99%